MARKETING OF SHEEP AND GOAT IN OGUN STATE OF NIGERIA - DIPEOLU, A.; MOMOH, S.; JAMIU, A.G. (Nigerian Journal of Animal Science, 2023)
Low consumption of sheep and goat in some parts of south western Nigeria can be attributed to short supply of livestock occasioned by inadequate marketing of the livestock. This study evaluated the structure, conduct and performance of the sheep and goat marketing in Ogun state by collecting data from both sellers and buyers in four markets in the four agricultural zones of the states. It was found that most of the retailers were in the economically active age group 25-40 years, consisting of both women and men. There were no wholesalers in the markets except in Sabo market. These set of people are from the northern parts of the country. The animals sold in these markets were obtained from the northern parts of the country. In Guffanti market, the animals are obtained from Alaba market which is a terminal market for small ruminants from the north. The lowest market concentration ratio (Gini coefficient) of 0.42 was obtained in Guffanti market showing that there was much competition among the retailers. Retail marketing margin ranged from N2'77.47 per head hf animal in Guffanti market to N445.71 per head in Imowo market. Analysis of variance test showed that there was significant difference in the net margin of the four markets at = 0.01. The contraints to increased small ruminant marketing included the extremely high purchase cost and the transportation cost of getting the animals down south which were almost twice the normal prices.